A descriptive Analysis of Anglicisms used in Ecuadorian Magazines. - Ortíz Carrillo, Bethzabé Yessenia (2011)
The use of anglicisms in the Spanish language has been studied in a few Spanish speaking countries such as Spain and Argentine. In addition, there is not an investigation about the use of anglicisms in writing media as magazines, which is one of the most influential ways of communication in our society.